### 1 Answer | Add Yours

We'll recall the equation of hyperbola:

x^2/a^2 - y^2/b^2 = 1

We'll recall the equation that gives the two asymptotes of hyperbola:

y = `+-` (b/a)*x

Comparing the given equation of hyperbola to the general equation, we'll identify a and b:

a = +6 or a = -6

b = +2 or b = -2

y = +(2/6)*x or y = -(2/6)*x

**The equations of the two asymptotes of the given hyperbola are: y = x/3 and y = -x/3.**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes